PERAN DESA PAKRAMAN DALAM PENGEMBANGAN PARIWISATA BUDAYA BERKELANJUTAN DI DESA BATUAN, SUKAWATI, GIANYAR - I Ketut Sakrabawa Diana; Dewa Ayu Lily Dianasari; Anom Hery Suasapha (JURNAL KEPARIWISATAAN, 2020)
Batuan is visited by domestic and international visitor for its cultural tourism attraction, in the form of a temple known as Pura Puseh Batuan or Puseh Batuan Temple. Puseh Batuan Temple is managed by the Batuan Customary Village as a sustainable cultural tourist attraction. But until now, little are known about the role of the customary village in developing the temple. This article discussed the role of Batuan Customary Village in developing it’s Puseh Temple as a sustainable tourism attraction. The research upon which this article written is a quantitative research done for the completion of a Bachelor Study. Data collected through survey to research sample selected from the villagers of Batuan Customary Village as the population. Quota sampling were used to determine the number of respondent surveyed from each of 8 localities in the Batuan Customary Village. Data collected were then analysed using regression technique. Results shows that the 3 (three) roles of Customary Village observed are partially and collectively significant in the evelopment of Puseh Batuan Temple as a cultural tourist attraction.